Assessment of genetic diversity in coriander (Coriandrum sativum) germplasm - B SENTHAMIZH SELVI; R CHANDRAKALA; SHARON ARAVIND; R SURESH; K VENKATESAN; M MOHANALAKSHMI; B A VAISHNAVI; D MASTAN VALI (The Indian Journal of Agricultural Sciences)
The present study was carried out during the winter (rabi) seasons of 2019–20 and 2020–21 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu, to examine the variability, correlation, path coefficient and genetic divergence among 275 coriander (Coriandrum sativum L.) accessions with four check varieties, viz. CO4, CO1, CO3, and CO2. The study utilized an augmented complete block design, which incorporated four checks. The study revealed significant variability among the coriander genotypes for key traits, indicating strong potential for improving coriander through selective breeding. High estimates of genetic coefficient of variation (GCV), phenotypic coefficient of variation (PCV), heritability and genetic advance were observed for the traits such as number of primary branches, number of secondary branches, number of umbels/plant, number of umbellets/plant, number of seeds/umbel, seed yield/plot and seed yield/plant. Correlation analysis showed a highly significant positive relationship between seed yield per plant and the number of seeds per umbel. Path analysis, however, suggested that both direct and indirect effects were relatively low, with the direct effect of the number of seeds per umbel being the most significant and positive. The genetic divergence analysis demonstrated that the accessions clustered into 10 distinct groups. Notably, cluster 4 contained highest number of accessions among all clusters, i.e. 48 and cluster 6 had only one accession. Principal component analysis revealed that PCA 1 showed maximum variances for yield traits while PC2, PC3 and PC4 showed maximum variances for yield attributing traits.